Transitions to new climates (TNCs) in the 21st century. (1st July 2022) - Giorgi, Filippo; Raffaele, Francesca
Abstract: We introduce the concept of transition to a new climate (TNC) based on ensembles of model projections. We consider a variable whose distribution due to interannual variability and inter-model spread of responses within a given time slice is measured by a certain compounded standard deviation, a TNC then occurs when the mean change signal of the variable between a future and a reference period exceeds the sum of the standard deviations for the two periods multiplied by a factor, taken here as 1.6 (see text). We calculate TNCs of regional mean annual surface air temperature from the CMIP6 ensemble of 21st century projections for 31 regions of the globe and four SSP scenarios. For the high-end scenarios, SSP5-8.5 and SSP3-7.0, we find the occurrence of at least one TNC in all regions and a second TNC in 15 and 10 regions, respectively, primarily located in tropical and mid-latitude regions and separated by about 40–45 years. For 30 out of 31 regions there is occurrence of a single TNC in the mid-level SSP2-4.5 scenario, while only 20 out of 31 regions experience a TNC in the low end SSP1-2.6. High latitude and polar regions tend to experience fewer and later occurring TNCs than low latitude ones, due to their larger interannual variability and inter-model response. On the one hand, the occurrence of at least one TNC, and in some scenarios and regions two TNCs, imply severe stress for adaptation of natural ecosystems and different socioeconomic sectors. On the other, the pronounced reduction of TNC occurrence in the low end scenarios point to the urgency of implementing effective mitigation policies to curb global warming.